O yoga e os benefícios no cotidiano e na saúde mental de participantes de grupo terapêutico: uma leitura pela terapia ocupacional - Yoshida, Karina Kaori (Universidade Federal de São Carlos, 2021)
Yoga is an Indian philosophical system aimed at the study of consciousness and self-knowledge. For some decades, it has been incorporated into the Public Health in Brazil, from the perspective of an integrative practice, as a strategy for promoting care and treatment. Occupational therapists are worked in with the Integrative and Complementary Practices, aiming at the construction of therapeutic projects that consider the subject's living spaces and their daily activities. The objective of this research was to analyze the benefits attributed to the practice of yoga in the mental and physical health of practitioners, from the improvement of symptoms and the performance of self-reported significant activities, correlating to the daily discussion in occupational therapy. The methodology used followed a qualitative framework, analyzing data from the research entitled “Characterization of the clientele of yoga groups in a university health service”, out of an instrument for investigating symptoms and activities and a survey of the participation in the groups; the second stage, bibliography research in academic texts and publications related to occupational therapy and daily life and the text Patañjali Yoga Sutras. The most frequently mentioned symptom was “anxiety” and the activity “study” indicated an important link to the academic environment. Most participants reported positive effects of yoga on symptoms that hindered activities that were meaningful to them in their daily lives, based on collective practices that prioritizes self-care techniques, self-knowledge and self-development, in order to balance the psycho-emotional and physical state. The study allowed articulations with the field of knowledge of occupational therapy, which in its interventions addresses the subject’s living spaces and the actions performed in daily life.
Yoga and its benefits in the daily life and mental health of a therapy group participants: a reading through the occupational therapy
Keywords: Ioga; Integralidade em saúde; Terapia Ocupacional; Cotidiano; Saúde mental; Yoga; Integrality in health; Occupational therapy; Daily life; Mental health; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; CIENCIAS DA SAUDE::SAUDE COLETIVA